Naloxone Alleviate the Severity of Delirium in Hospitalized Patients With Parkinsonism: Three Case Reports - Jin, Haiyan; Zhang, Jie; Hu, Qiongyue; Ping, Junjiao; Jiang, Tingyun; Du, Baoguo; Duan, Xin (Frontiers in Psychiatry, 2021)
Purpose: Delirium is common in older patients with Parkinson’s disease (PD). Treatments for delirium have generally been neuroleptics; however, antipsychotics have the potential to block striatal dopamine D2 receptors ensure worsen symptoms of parkinsonism. We explored whether naloxone can reverse delirium in PD and other forms of parkinsonism. Patients and methods: Patients with parkinsonism who met the criteria of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) for delirium received naloxone infusions once or twice daily. Treatment effects were evaluated using the Delirium Rating Scale-Revised 98 (DRS-R98), including non-cognitive and cognitive subscales; the Richmond Agitation–Sedation Scale (RASS); and the Mini-Mental Status Examination (MMSE). Results: We observed three patients with primary parkinsonism, one with vascular PD. The daily naloxone dose was 2.08 ± 0.64 mg (range: 1–4 mg) lasting from1 hour to 7 days; no side effects were observed. Reduced DRS-R98 scores within 12 hours and increased MMSE scores were observed followed by naloxone infusions. Significant improvements were observed in psychotic symptoms, disorientation, and attention deficits. RASS scores decreased under naloxone treatment. Conclusion: Naloxone reduced psychotic symptoms, improved cognitive dysfunction, and calmed emotional irritability in patients with delirium in the context of PD. The preliminary findings suggest that the opioid system may be involved in the pathophysiology of delirium. Further studies are warranted.